PENGARUH RASIO SARI KEDELAI DAN UMBI KENTANG TERHADAP KANDUNGAN GLUKOSA, PROTEIN DAN KECEPATAN LELEH MELLORINE - Novi Indah Puji Astuti; Rina Rifqie; Laili Hidayati (Journal of Food Technology and Agroindustry, 2023)
Mellorine is a type of dessert whose texture resembles ice cream by replacing some or all of the milk fat using Onabati fat. Vegetable fat from soymilk is commonly used in the manufacture of mellorine. The purpose of this study was to analyze the effect of the ratio of soymilk and potato tubers on the glucose, protein content and physical tests (melting speed and color) on mellorine. This type of research is an experimental study with two repetitions and three treatments, namely soymilk 80%: potato puree 20%, soymilk 70%: potato puree 30%, and soymilk 60%: potato puree 40% using a completely randomized design (CRD). One Way ANOVA was used to analyze the data and further tests will be carried out using DMRT. The results showed that there was a significant effect with a level of 5% on glucose content, protein and physical tests (melting speed and color).